THE IMPACT OF THE DIGITAL ECONOMY ON ECONOMIC GROWTH THROUGH EXPORT: EMPIRICAL STUDY IN ASEAN - Ninglis, Risti Wibawa; Prasetyo, Alvin Sugeng (Proceeding International Seminar of Islamic Studies, 2024)
This research examines and analyzes the impact of the digital economy on economic growth in ASEAN countries for the 2016-2022 period. This period is used because it is still in the era of the ASEAN economic community. The method used is the Generalized Moment Method. The estimation results show that exports significantly positively affect economic growth in ASEAN. This means that export activities are important to accelerate economic growth in ASEAN countries, especially in the ASEAN economic community era, so export activities need to be optimized. Furthermore, the interaction between trade and the digital economy positively relates to economic growth. This means that the digital economy can help encourage exports, so export expansion drives economic growth in ASEAN countries.